2016
DOI: 10.7554/elife.19850
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-mediated actin reset (CaAR) mediates acute cell adaptations

Abstract: Actin has well established functions in cellular morphogenesis. However, it is not well understood how the various actin assemblies in a cell are kept in a dynamic equilibrium, in particular when cells have to respond to acute signals. Here, we characterize a rapid and transient actin reset in response to increased intracellular calcium levels. Within seconds of calcium influx, the formin INF2 stimulates filament polymerization at the endoplasmic reticulum (ER), while cortical actin is disassembled. The reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
186
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 138 publications
(210 citation statements)
references
References 58 publications
(73 reference statements)
16
186
0
1
Order By: Relevance
“…CaAR initiates with a spike of intracellular calcium, which is immediately followed by polymerization of an “actin ridge” around the nucleus, loss of cortical actin but stiffening of the subcortical region, freezing of organelles, and changes in gene expression through myocardin-related transcription factors [Shao et al, 2015; Wales et al, 2016]. Polymerization of the actin ridge is INF2 dependent, and can stimulated by either the CAAX or non-CAAX isoform; for cells in which INF2 has been knocked down, neither polymerization nor other downstream effects occur [Shao et al, 2015; Wales et al, 2016]. While INF2 does not have a known calcium-sensing domain, Wales and colleagues demonstrated that in the presence of calcium, calmodulin binds INF2, pointing to a possible mechanism of activation [Wales et al, 2016].…”
Section: Inf2 and Cellular Actin Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…CaAR initiates with a spike of intracellular calcium, which is immediately followed by polymerization of an “actin ridge” around the nucleus, loss of cortical actin but stiffening of the subcortical region, freezing of organelles, and changes in gene expression through myocardin-related transcription factors [Shao et al, 2015; Wales et al, 2016]. Polymerization of the actin ridge is INF2 dependent, and can stimulated by either the CAAX or non-CAAX isoform; for cells in which INF2 has been knocked down, neither polymerization nor other downstream effects occur [Shao et al, 2015; Wales et al, 2016]. While INF2 does not have a known calcium-sensing domain, Wales and colleagues demonstrated that in the presence of calcium, calmodulin binds INF2, pointing to a possible mechanism of activation [Wales et al, 2016].…”
Section: Inf2 and Cellular Actin Structuresmentioning
confidence: 99%
“…Polymerization of the actin ridge is INF2 dependent, and can stimulated by either the CAAX or non-CAAX isoform; for cells in which INF2 has been knocked down, neither polymerization nor other downstream effects occur [Shao et al, 2015; Wales et al, 2016]. While INF2 does not have a known calcium-sensing domain, Wales and colleagues demonstrated that in the presence of calcium, calmodulin binds INF2, pointing to a possible mechanism of activation [Wales et al, 2016]. …”
Section: Inf2 and Cellular Actin Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Actin response to plasma membrane injury is biphasic, with initial depolymerization being followed by accumulation at the site of injury [148]. Cortical actin disassembly and reassembly in response to calcium increase occurs immediately after injury and is mediated by the formin INF2 [150]. Loss of cortical actin relieves membrane tension preventing the damaged free edges of the wound site from expanding outward and provides physical space to allow vesicles to fuse with the plasma membrane [14,62].…”
Section: Spatiotemporal Organization Of Signaling Elements and Effectorsmentioning
confidence: 99%